Asuhan Keperawatan Medikal Bedah Pada Pasien Dengan Bronkopneumonia Di Ruangan Paru RSUD Prof. H. M. Yamin, S. H Pariaman - Dian Eka Aulia Putri; Kheniva Diah Anggita; Linda Marni; Aulia Asman (CV. ITTC INDONESIA, 2026)
The phenomenon of bronchopneumonia as one of the lower respiratory tract infectious diseases is characterized by inflammation of the bronchi and alveoli caused by bacteria, viruses, or fungi. Bronchopneumonia may cause increased sputum production, shortness of breath, fever, impaired gas exchange, and respiratory failure complications. According to the World Health Organization (WHO) in 2023, bronchopneumonia as part of pneumonia caused approximately 2.6 million deaths worldwide each year. In Indonesia, the number of bronchopneumonia cases reached 446,437 cases in 2022. In West Sumatra Province, bronchopneumonia cases were recorded at 3,546 cases in 2021 and increased to 5,591 cases in 2022. Based on data from RSUD Prof. H. M. Yamin, S.H Pariaman, there were 44 bronchopneumonia cases in 2025. This study aimed to provide medical surgical nursing care for patients with bronchopneumonia in the Pulmonary Ward of RSUD Prof. H. M. Yamin, S.H Pariaman. The subject of this case study was Mrs. Z. The method used was direct observation to identify the patient’s problems. Nursing diagnoses found were ineffective airway clearance, ineffective breathing pattern, hyperthermia, and risk of infection. After five days of implementation, most nursing problems were resolved and the patient’s condition improved. Patients and families are advised to maintain a healthy lifestyle, comply with treatment, and avoid recurrence risk factors.